Emergence of activation or repression in transcriptional control under a fixed molecular context - Rosa Martinez-Corral; Dhana Friedrich; Robert Frömel; Lars Velten; Jeremy Gunawardena; Angela H. DePace (Proceedings of the National Academy of Sciences, 2025)
Transcription factors (TFs) can be both activators and repressors of gene transcription. This can manifest as “duality,” where the transcriptional response increases (activation) with TF concentration in one context but decreases (repression) in another context, or as “nonmonotonicity,” where, in the same context, the response increases in part of the concentration range and decreases outside that range. Here we use biophysical models of gene regulation to investigate how duality and nonmonotonicity relate to the interactions between a TF, Polymerase and the regulatory DNA. We distinguish two modes of TF action on Polymerase: “coherent,” with interactions either positive or negative, and “incoherent,” where interactions are a mix of both. For TFs that act incoherently from a single TF–DNA binding site, nonmonotonicity can arise, but only under nonequilibrium models. For single-site models, we show that nonmonotonicity can never happen under the common thermodynamic models of gene regulation, which consider equilibrium conditions and ignore the dissipative nature of the transcription process. Moreover, we show that merely changing the TF–DNA binding affinity, while keeping other features fixed, can tune the response between activation and repression, with responses either evaluated as a function of TF concentration or site number. Using the mammalian Sp1 as a case study and synthetically designed target sequences, we find experimental evidence for nonmonotonicity, and activation or repression tuned by affinity, which we interpret as evidence of incoherent action. Our work highlights the importance of moving from a TF-centric view to a systems view when reasoning about transcriptional control.